2016
DOI: 10.1007/s00430-015-0448-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of K65R in patients treated with tenofovir disoproxil fumarate: recommendations based on the Frankfurt HIV Cohort Study Resistance Database (FHCS-RD)

Abstract: Mutations in the genome of HIV-1 can compromise the success of antiretroviral treatments (ARTs) in HIV-1-infected individuals. The Frankfurt HIV Cohort Study Resistance Database (FHCS-RD) has previously documented a decline in the burden of resistance-associated mutations (RAMs) following the implementation of several new antiretroviral therapy regimens in 2007. In the current study, the annual burden of RAMs documented in the FHCS-RD in 2005-2013 was set in relation to the annual number of all cohort patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…However, although an increasing trend was identified in a cohort from India [ 56 ], several studies report a decrease on K65R levels over the years in other countries [ 48 , 57 , 58 , 59 , 60 ]. Reinheimer and colleagues suggest that the decline on K65R prevalence rates is linked with the increasing usage of single tablet ART regimens and the inclusion of AZT on the used treatment regimen, which has been liked with K65R development suppression [ 61 ]. Moreover, Theys et al work [ 59 ] suggests that the found decline of tenofovir K65R selection rate in Portugal, between 2002 and 2010, is mainly caused by changes on treatment guidelines over the years and by the increased usage of combination of TDF and emtricitabine (FTC) [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, although an increasing trend was identified in a cohort from India [ 56 ], several studies report a decrease on K65R levels over the years in other countries [ 48 , 57 , 58 , 59 , 60 ]. Reinheimer and colleagues suggest that the decline on K65R prevalence rates is linked with the increasing usage of single tablet ART regimens and the inclusion of AZT on the used treatment regimen, which has been liked with K65R development suppression [ 61 ]. Moreover, Theys et al work [ 59 ] suggests that the found decline of tenofovir K65R selection rate in Portugal, between 2002 and 2010, is mainly caused by changes on treatment guidelines over the years and by the increased usage of combination of TDF and emtricitabine (FTC) [ 59 ].…”
Section: Discussionmentioning
confidence: 99%